Attaining material sustainability by incorporating nanoparticles additives to improve the mechanical properties of polypropylene composites: Data driven modelling - Alsaffar M.A.; Ali J.M.; Abdel Ghany M.A.; Ayodele B.V. (IOP Publishing Ltd, 2023)
Additives; Forecasting; Graphene; Graphene Nanoplatelets; Neural networks; Planning; Plastic products; Support vector machines; Sustainable development; Tensile strength; Toughness; Cable insulation; Data driven modelling; Effect of parameters; Hybrid support vector machines; Maleic anhydride grafted polypropylene; Nanoparticles additives; Polypropylene composite; Research interests; Polypropylenes